Synthesis, Characterization, and Biological Evaluation of Chitosan Nanoparticles Cross-Linked with Phytic Acid and Loaded with Colistin against Extensively Drug-Resistant Bacteria - Fabian Pacheco; Alejandro Barrera; Yhors Ciro; Dorian Polo-Cerón; Constain H. Salamanca; José Oñate-Garzón (MDPI AG, 2024)
The natural evolution of microorganisms, as well as the inappropriate use of medicines, have accelerated the problem of drug resistance to many of the antibiotics employed today. Colistin, a lipopeptide antibiotic used as a last resort against multi-resistant strains, has also begun to present these challenges. Therefore, this study was focused on establishing whether colistin associated with chitosan nanoparticles could improve its antibiotic activity on an extremely resistant clinical isolate of Pseudomonas aeruginosa, which is a clinically relevant Gram-negative bacterium. For this aim, nanoparticulate systems based on phytic acid cross-linked chitosan and loaded with colistin were prepared by the ionic gelation method. The characterization included particle size, polydispersity index-PDI, and zeta potential measurements, as well as thermal (DSC) and spectrophotometric (FTIR) analysis. Encapsulation efficiency was assessed by the bicinchoninic acid (BCA) method, while the antimicrobial evaluation was made following the CLSI guidelines. The results showed that colistin-loaded nanoparticles were monodispersed (PDI = 0.196) with a particle size of around 266 nm and a positive zeta potential (+33.5 mV), and were able to associate with around 65.8% of colistin and decrease the minimum inhibitory concentration from 16 μg/mL to 4 μg/mL. These results suggest that the association of antibiotics with nanostructured systems could be an interesting alternative to recover the antimicrobial activity on resistant strains.